The Influence of Competence and Service Innovation on Work Discipline and Its Implications for the Effectiveness of Public Administration at the Department of Cooperatives, SMEs, Industry, and Trade of Tanjung Jabung Barat Regency - Maryani, Maryani; Suryani, Arna; Sudirman, Sudirman (Dinasti International Journal of Management Science, 2025)
This study aims to describe the competence, service innovation, work discipline, and effectiveness of public administration at the Office of Cooperatives, SMEs, Industry, and Trade of West Tanjung Jabung Regency. It also aims to test and analyze the influence of competence and service innovation on the effectiveness of public administration, both directly and indirectly through work discipline. This research was conducted at the Cooperatives, SMEs, Industry, and Trade Office of West Tanjung Jabung Regency. The population comprised 6,358 active MSMEs. The sample size used Slovin's theory with a 10% margin of error, resulting in 99 MSMEs. This study employed a quantitative approach with a survey method and Partial Least Squares (PLS) data analysis. The results of the study indicate that competence and service innovation directly and indirectly through work discipline have a positive and significant effect on the effectiveness of public administration, as well as work discipline directly and significantly affects the effectiveness of public administration. This means that if the Cooperatives, SMEs, Industry and Trade Office of West Tanjung Jabung Regency wants to improve the effectiveness of public administration, it is necessary to develop employee competence, encourage innovation in service, and build a strong work discipline culture as a foundation in realizing optimal bureaucratic performance.